Who cares? Paid sick leave mandates, care-giving, and gender - Tanya Byker; Elena Patel; Shanthi Ramnath (Federal Reserve Bank of Chicago, 2023)
We use employment data from the Current Population Survey to assess the efficacy of state-mandated paid sick leave policies on leave-taking behavior with a focus on any variation by gender. We find that these policies increase leave taking for care-giving for men by 10-20%, and this effect is strongest for men with young children in the household. In addition, we find that Hispanic men and men without a bachelor's degree, who historically have had low access to paid sick leave, are 20-25% more likely to take care-giving leave. By comparison, we do not find evidence that these policies affect leave taking for own sickness for men or women, nor do we find evidence that these policies affect care-giving leave taking for women. Our evidence highlights the importance of studying care-giving leave within the context of paid leave policies and the importance of considering gender differences in the treatment effect within this context.
Keywords: H31; J14; J38; 330; Paid Sick Leave; Care-Giving Leave; Gender; Leave Taking